2004
DOI: 10.2165/00126839-200405050-00001
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Factors Determining the Pharmacokinetics and Antiviral Activity of HIV-1 Non-Nucleoside Reverse Transcriptase Inhibitors of the Diaryltriazine and Diarylpyrimidine Classes of Compounds

Abstract: We observed correlations between exposure in humans with exposure in rats, transepithelial transport (Caco-2 cells), ionisability, lipophilicity, aggregate radius and SASA in the class of DATA/DAPY NNRTI compounds. The lipophilic DATA/DAPY compounds form aggregates. It can be assumed that absorption in the intestinal tract and endocytosis in infected cells of these lipophilic compounds are governed by the common phenomenon of aggregate formation. As the lymphatic system offers a pathway for intestinal uptake o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 30 publications
5
43
0
Order By: Relevance
“…Dapivirine presented P app values (mean ± SD) of 3.70 × 10 −6 ± 0.36 × 10 −6 and 4.44 × 10 −6 ± 0.26 × 10 −6 cm s −1 for CaSki and Caco-2 cell monolayers, respectively, when dapivirine-loaded nanoparticles were used; in the case of the free drug, these results increased to 4.84 × 10 −6 ± 0.28 × 10 −6 and 5.26 × 10 −6 ± 0.38 × 10 −6 cm s −1 for CaSki and Caco-2 cell monolayers, respectively. Even if higher, the values found in this study are in order with those previously reported for free dapivirine in Caco-2 cell monolayers (2.14 × 10 −6 ± 0.81 × 10 −6 cm s −1 ) [35].…”
Section: Methods Applicabilitysupporting
confidence: 91%
“…Dapivirine presented P app values (mean ± SD) of 3.70 × 10 −6 ± 0.36 × 10 −6 and 4.44 × 10 −6 ± 0.26 × 10 −6 cm s −1 for CaSki and Caco-2 cell monolayers, respectively, when dapivirine-loaded nanoparticles were used; in the case of the free drug, these results increased to 4.84 × 10 −6 ± 0.28 × 10 −6 and 5.26 × 10 −6 ± 0.38 × 10 −6 cm s −1 for CaSki and Caco-2 cell monolayers, respectively. Even if higher, the values found in this study are in order with those previously reported for free dapivirine in Caco-2 cell monolayers (2.14 × 10 −6 ± 0.81 × 10 −6 cm s −1 ) [35].…”
Section: Methods Applicabilitysupporting
confidence: 91%
“…Typically, drugs with Log P values in the range of 2 to 3 show optimal permeability across the stratum cornea (SC), as well as moderate partitioning out of the SC. On the contrary, drugs with a Log P of Ͼ3 are expected to exhibit high partitioning into the SC but poor partitioning into the systemic circulation (22). It is known that lipophilic compounds have higher tissue residence times and therefore lower systemic exposure (10).…”
Section: Discussionmentioning
confidence: 99%
“…It thus appears that there is a minimum threshold on the number of molecules that are required to inhibit virus reproduction in an infected cell. 42,43 It is known that lipophilic compounds (such as TMC120 and R278474) can form aggregates. 44 Formation of aggregates is common, and it may be the cause of nonspecific binding to proteins that has been observed in high-throughput screening (HTS) tests.…”
Section: Requirement 2: High Oral Bioavailability and Long Eliminatiomentioning
confidence: 99%